Quantifying key parameters as elicitors for alternate fruit bearing in cv. 'Elstar' apple trees - Krasniqi, Anne-Lena (Plant science : an international journal of experimental plant biology, 2013)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.